Anatomists: New members of the disability advocacy team. Issue 11 (16th May 2021) - Hoffmann, Darren; Robertson, Ellen
Abstract : What would you say if we told you that there is a group of faculty at virtually every health professions school who (1) are knowledgeable in the wide variation of body shapes, sizes, and ability level; (2) are skilled in teaching concepts of form, function, and altered function; and (3) work with students at the very beginning of their training, often with nearly 100 hours of face time? Perhaps you'd say, "Please introduce me to these magical people!" Well, we would like to introduce you to anatomists, occupants of a role in medical education as old as medicine itself. Anatomists are experts in how the body works and sometimes works differently. Anatomists are the keepers of the language of the body. And as the two of us have recently learned, we are scientists and educators who are well positioned to support a positive disability culture in health science education.